Investigating reservoir-triggered seismicity in the Koyna–Warna region through nodal ambient noise tomography - Pratul Ranjan; Prakash Kumar; Biswajit Mandal; Periyasamy Karuppannan (Scientific Reports)
Abstract The Koyna–Warna region in southern India is a unique case of dual Reservoir-Triggered Seismicity (RTS), surrounding impoundments on Koyna and Warna rivers. In this study, we perform ambient noise surface wave tomography using data from a temporary dense deployment of three-component geophones in order to understand the origin of RTS. To achieve this objective, surface wave dispersion curves from noise cross-correlations in rotated coordinates were used to create group velocity maps in 0.5–5 s periods. The group velocity dispersions from map bins were inverted for shear wave velocity ( $$V_s$$ ) and $$V_s$$ radial anisotropy ( $$ξ$$ ) maps down to 5 km depth. The $$V_s$$ and $$ξ$$ till 1 km depth are correlated with topographical features in agreement with the basement depth estimates. Large earthquakes in the region are marked by negative $$ξ$$ with negative $$V_s$$ anomaly or $$V_s$$ anomaly contrast, suggesting shear strength could be an important control on their genesis. A large negative $$V_s$$ anomaly southwest of the Koyna reservoir is linked with reservoir water migration to greater depths, part of a larger interconnected system of pathways extending across the reservoirs. These results, set decades post reservoir impoundment, can help understand the evolution of RTS around dam sites elsewhere.